Efektivitas, Bebeja, Digitalisas EFEKTIVITAS APLIKASIBEBEJA MENUJU DIGITALISASI PEMERINTAHAN KABUPATEN PANDEGLANG - Muhammad Taufik Harsana (NIAGARA Scientific Journal, 2022)
After the ratification of Presidential Regulation No. 76 of 2013 concerning handling public service complaints. Since August 17, 2017 the Pandeglang Regency government has opened a public complaint service in the form of complaints through an application called Bebeja. Services in electronic form are highly expected by the public, because they are felt to be effective, especially in terms of complaints. Therefore the author feels the need to know the effectiveness of these services. The effectiveness of public complaint services through the Bebeja application can be determined using the theory of effectiveness according to Siagian (2013: 20-21) with the dimensions: (1) Resources, funds, facilities and infrastructure (2) Quantity and quality of goods (3) Deadline. (4) Procedures that must be followed in completing the task. This research uses a descriptive research type with a qualitative approach. The results of this study indicate that the research results obtained are: 1) Resources, funds, facilities and infrastructure, are in accordance with applicable regulations and are able to support the smooth running of service activities 2) The number and quality of services produced, the number of people participating in this service and quality of service that can reflect the accuracy of reports and ease of service 3) The time limit, the complaint service process is appropriate 4) The service procedures that must be taken are in accordance with KEMENPAN Number 63 of 2003 where public service providers must fulfill several principles, one of which is simplicity.